2012
DOI: 10.1088/0004-637x/752/2/157
|View full text |Cite
|
Sign up to set email alerts
|

RADIATION MECHANISMS AND PHYSICAL PROPERTIES OF GeV–TeV BL Lac OBJECTS

Abstract: Broadband spectral energy distributions (SEDs) simultaneously or quasisimultaneously observed with Fermi/LAT and the other instruments are complied from literature for 24 TeV BL Lac objects. Two SEDs are available for each of 11 objects, and the state of the sources is identified as a low or high state according to its flux density at 1 TeV. The well-sampled, clean SEDs without contaminations of the accretion disk and external Compton process of these sources are the best candidates for investigating the radia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

32
274
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 165 publications
(307 citation statements)
references
References 102 publications
32
274
1
Order By: Relevance
“…It should be cautious that the opacity effect just give the lower limit for the Lorentz factor, which is energy dependent (e.g., depend on the photons at highest energy) and this gives the uncertainties in the above explanation. It is interesting to note that the derived Lorentz factors from the transparency condition in GRBs and blazars are normally just several times lower than that derived from other independent methods (e.g., Zou & Piran 2010;Zhang et al 2012), which suggests that above explanation based on transparency condition may be reasonable.…”
Section: Conclusion and Discussionmentioning
confidence: 89%
“…It should be cautious that the opacity effect just give the lower limit for the Lorentz factor, which is energy dependent (e.g., depend on the photons at highest energy) and this gives the uncertainties in the above explanation. It is interesting to note that the derived Lorentz factors from the transparency condition in GRBs and blazars are normally just several times lower than that derived from other independent methods (e.g., Zou & Piran 2010;Zhang et al 2012), which suggests that above explanation based on transparency condition may be reasonable.…”
Section: Conclusion and Discussionmentioning
confidence: 89%
“…This is a situation frequently encountered in the models of TeV BL Lac objects (e.g., Tavecchio et al 2010;Aleksić et al 2011;Mankuzhiyil et al 2012;Zhang et al 2012). …”
Section: Multiwavelength Spectral Energy Distributionmentioning
confidence: 91%
“…Specifically, the relatively flat power law spectrum measured by XRT is inconsistent with a rapidly (exponentially) decreasing spectrum that an exponential cut-off would predict. Indeed, this is the typical situation encountered in the modelling of these sources, motivating the use of phenomenological electron spectra as applied here (see, e.g., Tavecchio et al 1998;Zhang et al 2012) or similar (e.g., the log-parabola distribution discussed in Tramacere et al 2011), which provide more symmetric peaks in the SED.…”
Section: Multiwavelength Spectral Energy Distributionmentioning
confidence: 98%
“…Different authors have successfully modeled its emission using a simple one-zone SSC model (Albert et al 2007;Abdo et al 2010;Aleksić et al 2010;Tavecchio et al 2010;Zhang et al 2012). However, the uncertainty in the distance of this object complicates the modeling task and indeed most solutions adopted redshift values which have later been proven to be incorrect.…”
Section: Introductionmentioning
confidence: 99%
“…Albert et al (2007) successfully modeled the SED assuming z = 0.3, and found that for z > 0.56 the emission from PG 1553+113 is not compatible with a simple onezone SSC model. Aleksić et al (2010) and Zhang et al (2012) also presented a successful one-zone SSC model assuming z = 0.3, while Tavecchio et al (2010) assumed z = 0.36. Abdo et al (2010) successfully modeled the SED of PG 1553+113 assuming z = 0.75, but they needed unusual values for the emitting region size (R 10 18 cm, that is a factor of at least ten larger than usual SSC modeling) and an ad-hoc double-broken power-law distribution for the electrons.…”
Section: Introductionmentioning
confidence: 99%